2000
DOI: 10.1677/joe.0.1670175
|View full text |Cite
|
Sign up to set email alerts
|

Functional inactivation of the IGF-I receptor delays differentiation of skeletal muscle cells

Abstract: Skeletal myoblasts are inherently programmed to leave the cell cycle and begin the differentiation process following removal of exogenous growth factors. Serum withdrawal results in a marked induction of IGF production which is essential for skeletal muscle differentiation in vitro. However, the potential role of the tyrosine kinase IGF-I receptor (thought to be the principal mediator of both IGF-I and II signaling in skeletal muscle) in the decision of myoblasts to begin differentiation following serum withdr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 41 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…Moreover, the IGF-I receptor expression during muscle cell differentiation may be regulated through autocrine production of IGF-II [34,35]. Functional inactivation of the IGF-I receptor caused a delay of differentiation in mouse skeletal muscle cells [36]. We found that IGF-I receptor mRNA expression tended to increase with differentiation in porcine muscle cell cultures.…”
Section: Basal Expression Of Igf-i Igf-ii Egf and Their Receptors Imentioning
confidence: 64%
“…Moreover, the IGF-I receptor expression during muscle cell differentiation may be regulated through autocrine production of IGF-II [34,35]. Functional inactivation of the IGF-I receptor caused a delay of differentiation in mouse skeletal muscle cells [36]. We found that IGF-I receptor mRNA expression tended to increase with differentiation in porcine muscle cell cultures.…”
Section: Basal Expression Of Igf-i Igf-ii Egf and Their Receptors Imentioning
confidence: 64%
“…Thus, the data reported in the present study suggest that increases in IGF-IR numbers and specific binding might be related to the differentiation of the primary gilthead sea bream myocytes. Indeed, functional inactivation of the IGF-IRs delays the differentiation of C2C12 muscle cells (Cheng et al 2000), whereas overexpression of IGF-IRs accelerates myogenic differentiation (Quinn et al 1994;Quinn and Haugk 1996).…”
Section: Discussionmentioning
confidence: 99%
“…IGFs are thought to stimulate muscle cell proliferation and differentiation in culture through interaction with the IGF-IR (Ewton et al 1987;Duclos et al 1991;Galvin et al 2003), thereby stimulating tyrosine kinase activity and the activation of the MAPK signalling pathway during proliferation (Coolican et al 1997) and differentiation (Wu et al 2000) in various cell in vitro model systems. In addition, this binding process activates the PI3K/Akt pathway during differentiation (Coolican et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of a mutant type I IGF-I receptor that is unable to autophosphorylate reduces myoblast differentiation upon serum withdraw (40). Conversely, increasing expression of the type I IGF-I receptor promotes spontaneous differentiation of myoblasts (41).…”
Section: Discussionmentioning
confidence: 99%